Vpeljava simulacij kot sodobne metode učenja in poučevanja na dodiplomskem študiju zdravstvene nege: opisna raziskava - Karnjuš, Igor; Prosen, Mirko; Ličen, Sabina (Revija za elementarno izobraževanje, 2020)
The aim of our study was to evaluate the learning experiences of undergraduate nursing students enrolled in an Advanced Life Support (ALS) simulation course, by using a patient simulator. Seventy-three undergraduate nursing students from the third year evaluated a simulation-based ALS course, using statements scored on a five-point Likert scale and three open-ended questions. Students believe that simulations are an efficient method for learning that facilitates the integration of theoretical knowledge into everyday clinical practice. Although 16 students stated that this experience was slightly stressful, all students were of the opinion that they would like to have more opportunities to learn through simulations.